Main Directions of Poverty Reduction in the Areas - Turdimuratov Maksud Muzaffarovich (Researchparks Publishing, 2022)
It should be noted that the distributional effect of income distribution on the population is twofold, it represents the achievement of prosperity as a result of the steady increase in the income of the employed and the distribution of social efficiency, on the contrary, it represents an increase of poverty. The poor are not only deprived of the opportunity to benefit from rapid economic growth, but also unable to contribute to development due to limited opportunities to participate in various sectors of society.